Production of bacterial cellulose fibers in the presence of effective microorganism. Issue 4 (19th May 2019) - Gunduz, Gokhan; Erbas Kiziltas, Esra; Kiziltas, Alper; Gencer, Ayhan; Aydemir, Deniz; Asik, Nejla
ABSTRACT: In this study, effective microorganism (EM) was added into fermentation medium in static culture to enhance bacterial cellulose (BC) production by Acetobacter xylinum 23769 strain. According to SEM micrographs, BC pellicles from BC-Baikal EM1 show a smaller diameter and a relatively narrow diameter distribution compared to BC pellicles from Hestrin–Schramm (HS) medium. The BC-HS absorbed 90.5 times its dry weight of water. The water holding capacity increased to 132.5 for BC-Baikal EM1 medium compared to BC-HS. From the FT-IR spectra, BC samples exhibited a similar pattern. The crystalline indices of Baikal EM1-altered BC (66%) were lower than Baikal EM1-free BC (71%).